2020
DOI: 10.3390/su12072902
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Point in the Evacuation Drills: Analysis of Eye Movement at the Indoor Wayfinding

Abstract: Signage systems are the main means of resolving the wayfinding problem in an emergency evacuation. However, recent literature has proven that signage systems are often not effective in an indoor wayfinding decision-making situation. Many studies that attempted to solve the problem did not consider the interaction between the optimal location of signage systems and gaze characteristics. Therefore, this study aimed to provide basic database to determine the optimal location of signage by analysing the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The lowest average DMTs were observed at y = 270 cm for the left arrow direction and at y = 150 cm for the right arrow direction. These results appear to be similar to the results of previous studies [26] in which the optimal installation location of the signs was proposed based on the analysis of the gaze point and eye movement data of the participants. In previous studies, the eye movement data obtained while the participants passed through the 2-m high maze-set were analyzed, and the gaze points of the evacuees were quantified in the horizontal and vertical directions according to the type of junction and corridor in which wayfinding decisions occurred.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lowest average DMTs were observed at y = 270 cm for the left arrow direction and at y = 150 cm for the right arrow direction. These results appear to be similar to the results of previous studies [26] in which the optimal installation location of the signs was proposed based on the analysis of the gaze point and eye movement data of the participants. In previous studies, the eye movement data obtained while the participants passed through the 2-m high maze-set were analyzed, and the gaze points of the evacuees were quantified in the horizontal and vertical directions according to the type of junction and corridor in which wayfinding decisions occurred.…”
Section: Discussionsupporting
confidence: 90%
“…Vertical heights between 100 and 150 cm attracted the gaze of the largest number of people, and vertical heights between 0 and 50 cm attracted the gaze of the fewest number of people. Although a direct comparison cannot be performed, owing to the different heights of the walls used in the experiment (2 m for the previous studies [26] and 3 m for this study), the average DMTs seemed higher in this study when the participants observed the signs installed at low locations as with the results of the previous studies, because the participants were less likely to notice the low locations of the wall. Therefore, the experimental results of this study indicate that the installation of signs at the low locations of the wall is highly likely to adversely affect the DMTs of occupants in an evacuation situation.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Studies have been conducted on the objective factors influencing guidance indicators, the identification of the guidance system by traffic, and the application of topological networks using route-related and spatial relationships [16]. An effective navigation system can guide people to their destination and improve tourist safety [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eye-tracking glasses headsets can be used to pinpoint signi cant visual cues. Previous research has found that some evacuation signs are improperly placed and remain entirely unnoticed during evacuation (Bae et al, 2020). Environmental characteristics also affect decision-making.…”
Section: Introductionmentioning
confidence: 99%